Bone marrow mesenchymal stem cell derived exosomal miR-455-5p protects against spinal cord ischemia reperfusion injury. (February 2022) - Liu, Bing; Zheng, Wenjun; Dai, Li; Fu, Shengjie; Shi, Enyi
Highlights: Exosomal miR-455-5p alleviates spinal cord ischemia reperfusion (SCIR) injury. Exosomal miR-455-5p inhibits apoptosis of neurons in the injured spinal cord. Exosomal miR-455-5p activates autophagy pf neurons in the injured spinal cord. Abstract: At present, much more studies have focused on the therapeutic effect of exosome-delivered microRNAs on diseases. Previous study has shown that miR-455-5p is downregulated in ischemic stroke, but little is known about the role of exosome-delivered miR-455-5p in spinal cord ischemia reperfusion (SCIR) injury. Herein, we isolated exosomes from bone marrow mesenchymal stem cells (BMSCs) transfected with lentivirus vectors containing miR-455-5p. SCIR rat model was established after the intrathecal injection of exosomes containing miR-455-5p. The expression level of miR-455-5p was downregulated after SCIR, administration of exosomal miR-455-5p enhanced the level of miR-455-5p in the injured spinal cord. Hind-limb motor function scores indicated that exosomal miR-455-5p improved the recovery of hind-limb function of SCIR rats. HE staining and Nissl staining showed that miR-455-5p enriched exosomes reduced histopathological abnormalities after SCIR. Double immunofluorescence staining revealed that exosomes containing miR-455-5p reduced apoptosis of neurons, and activated autophagy in neurons after SCIR. We observed that the expression of Nogo-A, a direct target of miR-455-5p, was decreased in the spinal cord of exosomal miR-455-5p administrated SCIR rats. Targeting relationship between miR-455-5p and Nogo-A was verified by dual-luciferase reporter assay. In summary, exosomes containing miR-455-5p had the neuroprotective effects on SCIR injury by promoting autophagy and inhibiting apoptosis of neurons.